THE CONSTITUTIONAL COURT’S PROGRESSIVE DECICIONS ON SOLVING THE REGIONAL HEAD ELECTION DISPUTE - Meyrinda R. Hilipito (Widyariset, 2012)
The Constitutional Court of the Republic of Indonesia has been putting all the efforts to uphold a substantivejustice in every decision since its establishment, eight years ago. However, in relation with the regional headelection disputed, the court has made progressive decisions. Therefore, it seems that the court has been trying toextend its own authority. To analyze the problem, the research uses normative judicial research. Four court decisionsover the disputes of district elections that will be examined are the one of East Java Province, South Bengkulu,Kotawaringin Barat, and Jayapura. Based on the analysis of this research, the court has made progressivelegal interpretations. It means that the court is promoting substantive justice rather than procedural one.